ДАМЫҒАН МЕМЛЕКЕТТЕРДЕ ВЕНЧУРЛЫҚ БИЗНЕСТІҢ ДАМУ ТƏЖІРИБЕСІ - Садыкова, А (Journal of Economic Research & Business Administration, 2015)
For the implementation of the global economy, we need to produce competitive products, and venture business development contributes to this. If we develop a business venture in Kazakhstan, the experience of developed countries, this will bring big profits in our economy. The union of Kazakhstan in all the peace level of industrialized countries establishes a single national economy.